Indikator Planned Behavior Theory dan Tipe Kepribadian sebagai Determinan Minat Mahasiswa Mengikuti Pendidikan Profesi Akuntan - Darmiti, Ni Kadek; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 32 No 5 (2022), 2022)
Accountant Profession Education (PPAk) plays an important role to improve the professionalism of accountants in the future, although there are still relatively few accounting graduates in Indonesia who are interested in following PPAk. This study aims to empirically test the determinants of students interests following PPAk in terms of theory of planned behavior and personality type. Data was collected through survey methods by distributing questionnaires to students of semester 7 of the Accounting Undergraduate Study Program of the Faculty of Economics and Business, Udayana University. The sample was taken using a simple random sampling method obtained by 148 respondents. The analysis technique used is Partial Least Square (PLS). The results of the analysis showed that attitudes towards behavior, subjective norms, control of perceptual behavior, and personality type A had a positive effect on students interests in following PPAk. Keywords: Interests; Attitudes; Norms; Behaviors; Personalities.